Accounting Decision Making: Psychological and Sociological Perspectives - Grana Koeswardani; Sri Trisnaningsih (International Journal of Economics and Management Sciences, 2025)
This exploratory study is the influence of individual psychology on the development of acculturation through the integration of psychological and social perspectives. The purpose of this study is to provide a better understanding how psychological and social factors influence statements made in the accounting context. Using a multidisciplinary approach, this study identifies and analyzes cognitive biases, social norms, and group dynamics that influence the process of developing acceptance attitudes. The findings of the study indicate that psychological biases such as overconfidence, self-isolation, and herd behavior have a significant impact on attitudes held by individuals and groups. In addition, psychological factors such as social support and organizational culture take an important part in fostering trust. In the hope of providing more detailed information on how psychological and social elements interact in the accounting context.